The Status and Actions of the 25th Istanbul-based 25th Corps during the Armistice Period - Enes Mert Demir (Tarih Dergisi)
The Ottoman army was organised as 9 corps after the Armistice of Mondros. One of these corps was the 25th Corps, which had its headquarters in the capital Istanbul. The 25th Corps, which was stationed on the Istanbul-Izmit line with the 1st Division and the 10th Caucasian Division under its command, was the only corps that could not directly participate in the National Struggle due to the occupation of the capital. However, the 1st Division in Izmit came under the command of Ankara in time. This study examines the organisational structure and activities of the 25th Corps, about which there is no original study. Thus, it is aimed to explain the status of the Corps during this period. The sources of the study are the documents in the Ottoman Archive and ATASE Archive and the literature on the period. The findings obtained were evaluated with the qualitative analysis method in the perspective of the political and military developments of the period.